Diabetic neuropathhy assessed at two time points five years apart - Alajbegović Kurtović, Azra (Array, 2008)
Summary: Patients with either type 1 or type 2 diabetes mellitus (DM) carry a risk of developing chronic diabetic complications. The aim of the study was to establish the prevalence of diabetic neuropathy in 300 patients with type 1 and 2 diabetes evaluated at two time points 5 years apart. The study included 300 patients with clinically diagnosed and laboratory verified diabetes. Initial examination, questionnaire and laboratory testing were performed in all patients in 1999 (type 1diabetes 62 patients and type 2 diabetes 238 patients).Final examination, questionnaire and laboratory testing were performed in 2004 in 278 patients (type 1diabetes 58 (20.9%) patients and type 2 diabetes 220 (79.1%) patients).Additional history taken on 2004 examination placed two female patients previously classified as type 2 diabetes to another specific diabetes type group.Twenty patients died in the period between March 31, 2000 and final examination taken on February 1, 2004. In 1999, 51.1% of patients had diabetic neuropathy; in 2004, symptoms and signs of diabetic polyneuropathy were recorded in 84.2% of the same diabetic population.The increase in the number of patients with diabetic neuropathy recorded during the 5-year period was statistically significant.The average duration of diabetes was 13 years at initial examination and 18 years at final examination.In conclusion, diabetic neuropathy was significantly more common in 2004 than in 1999 in the same group of patients (p<0.01).The risk of developing diabetic neuropathy increased with longer duration of diabetes (p<0.05). Therefore, a more aggressive approach is necessary in the treatment of our diabetic patients, including education, physical activity and use of appropriate medication